Game Education “Fruit Shooter” Berbasis Android - Paryanta - STMIK AUB Surakarta (APMMI - Asosiasi Profesi Multimedia Indonesia, 2019)
Abstract - The development of Game Technology circulating in the community is mostly used by children for games that are less beneficial for children. Many parents feel anxious about their children who play games every day until they forget the time to study via their smartphone. Based on the problems faced by the parents above, the authors developed an educational and edutainment or Android-based educational game that is useful for children helping in their learning activities. Game development methods use the Waterfall method while game design uses storyboarding and Unified Modeling Language (UML), while this game is built using java programming language with Unity software. The results of this research have produced a game called